Islamic Education Supervision: A Conceptual Analysis in Strengthening Educational Quality Management - Rusmini, Rusmini; Hasnidar, Yuni; Zahro, Fatimatuz (Universitas Pahlawan Tuanku Tambusai, 2026)
This study is motivated by ongoing quality issues in Islamic education, particularly the limited effectiveness of supervision as an integral component of the educational management system. In practice, supervision is often reduced to a mere administrative activity, which undermines its potential role in improving educational quality. This article aims to conceptually examine Islamic education supervision within the framework of educational quality management by addressing the following key questions: (1) how is supervision conceptually positioned within Islamic education quality management, and (2) what strategic roles does supervision play in strengthening educational quality governance? Using a qualitative approach through a literature review and conceptual analysis of relevant scholarly sources, this study finds that Islamic education supervision holds a strategic function as a mechanism of control, evaluation, and quality assurance within the management system. Beyond monitoring, supervision serves as a managerial instrument that supports the sustainable enhancement of governance and quality improvement in Islamic educational institutions. This article contributes theoretically to the discourse on Islamic education supervision and offers managerial insights for strengthening quality management practices.